Keteladanan Kepemimpinan Rasul Paulus sebagai Role Model dalam Pengembangan Sumber Daya Manusia Berdasarkan Efesus 4:1-16 di Gereja Bahagian Bahasa Melayu di Negara Brunei Darussalam - Render Luwis (Sekolah Tinggi Teologi Berita Hidup, 2020)
Abstract: The leader is the person who carries out the process, behavior or relationship. In this case the leader must have leadership qualities that are based on the based on the universal characteristics of a leader, for example, having this research is a literature study or literature review using reference books that contain a discussion about the leadership of the Apostle Paul as a role model in human resources development based on Ephesian 4:1-16 by applying descriptive methods. The leadership model of the Apostal Paul based on Ephesians 4:1-16 as the Role of the Gereja Bahagian Bahasa Melayu Human Resource Development Model in the State of Brunei Darussalam as follows: First the character of Christ-likeness. Second, the unity of believers because God is one which is the doctrinal expected by God to be the basis of theology of believers is that the believer must be able to maintain the unity of the Spirit by the bond of peace, not letting or even confounding. Third, unity of service by sharing gifts is God’s gift to believers to serve Him. Forth, the unity of being the perfect body or Christ is a process of believers throughout life continuously tirelessly focused to grow to be perfect.Abstrak: Pemimpin adalah orang yang melaksanakan proses, perilaku atau hubungan. Dalam hal ini pemimpin harus mempunyai kualitas kepemimpinan yang berbasiskan ciri universal seorang pemimpin, misalnya mempunyai Penelitian ini merupakan kajian literatur atau kajian pustaka dengan menggunakan buku-buku referensi yang memuat bahasan mengenai kepemimpinan Rasul Paulus sebagai role model dalam pengembangan Sumber Daya Manusia berdasarkan Efesus 4:1-16 dengan menerapkan metode deskriptif. Kesimpulan: Keteladanan Kepemimpinan Rasul Paulus berdasarkan Efesus 4: 1-16 sebagai Role Model Pengembangan Sumber Daya Manusia Gereja Bahagian Bahasa Melayu di Negara Brunei Darussalam sebagai berikut berikut: Pertama, karakter seperti Kristus. Kedua, kesatuan orang percaya karena Allah adalah satu adalah doctrinal yang diharapkan oleh Tuhan menjadi dasar teologi orang percaya adalah bahwa orang percaya wajib mampu memelihara kesatuan Roh oleh ikatan damai sejahtera, bukan membiarkan atau bahkan mengacaukan. Ketiga, kesatuan melayani dengan berbagai karunia merupakan pemberian Allah kepada orang percaya agar mereka melayani-Nya. Keempat, kesatuan menjadi tubuh Kristus yang sempurna merpakan proses orang percaya sepanjang hidup terus-menerus tanpa mengenal lelah fokus untuk bertumbuh menjadi sempurna